2015
DOI: 10.1016/j.nbd.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic and behavioral effects of long-term voluntary exercise in wild-type and APP-overexpressing transgenics

Abstract: Physical exercise may provide protection against the cognitive decline and neuropathology associated with Alzheimer’s disease, although the mechanisms are not clear. In the present study, APP/PSEN1 double-transgenic and wild-type mice were allowed unlimited voluntary exercise for 7 months. Consistent with previous reports, wheel-running improved cognition in the double-transgenic mice. Interestingly, the average daily distance run was strongly correlated with spatial memory in the water maze in wild-type mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…However, although it has been proposed that physical exercise protects against the development of AD [65], it remains unclear whether it is beneficial after the onset of the disease. Indeed, several studies suggest that exercise fails to increase neural plasticity in animal models and AD patients [67,68]. To demonstrate whether GSK-3b overexpression interferes with the stimulatory actions of physical exercise, we subjected the retrovirus-injected mice to a period of voluntary wheel running (Fig.…”
Section: Development Of a Novel Methodology To Study The Cell-autonommentioning
confidence: 99%
“…However, although it has been proposed that physical exercise protects against the development of AD [65], it remains unclear whether it is beneficial after the onset of the disease. Indeed, several studies suggest that exercise fails to increase neural plasticity in animal models and AD patients [67,68]. To demonstrate whether GSK-3b overexpression interferes with the stimulatory actions of physical exercise, we subjected the retrovirus-injected mice to a period of voluntary wheel running (Fig.…”
Section: Development Of a Novel Methodology To Study The Cell-autonommentioning
confidence: 99%
“…Interestingly, previous studies have found that the effects of EE in Alzheimer´s animal models were observed after complex enrichment (enriched environment plus exercise) but not after exercise alone [ 125 , 148 ]. However, a recent study [ 149 ] has found that voluntary exercise improved the memory performance in the APP/PSEN1 double-transgenic mouse model, although the amount of daily exercise was not correlated with spatial performance. As previously mentioned, EE is a stimulation protocol also involved in the recovery from different sorts of brain damage [ 150 ].…”
Section: What Is the Environmental Enrichmentparadigm?mentioning
confidence: 99%
“…One of the conclusions from the Maesako et al study [ 126 ] was that exercise improved memory in the MWM better than diet control. This seems reasonable given that exercise offers some of the same benefits as diet control, such as weight loss and decreased adiposity; however, unlike diet control exercise can also increase neurogenesis and improve cardiovascular health [ 131 ], and can induce changes in synaptic and cytoskeletal proteins to different extents in wildtype and AD mutant mice [ 132 ]. Furthermore, in rodents, even short-term (6 weeks) environmental enrichment, in the absence of physical activity, has been shown to improve spatial learning and working memory performance, in addition to increasing neurogenesis and synaptogenesis in the dentate gyrus [ 133 ].…”
Section: Inflammation Is Related To Cognitive Deficitsmentioning
confidence: 99%